Prenatal light exposure affects diurnal rhythms and visual development of the layer embryonic retina - S.Q. Wei; P. Yin; W.Y. Tang; Z.Y. Zhang; W. Chu; Q. Tong; B.M. Li; W.C. Zheng; C.Y. Wang (Poultry Science, 2025)
It is believed that some wavelengths of light penetrate through eggshell and are perceived by avian embryo, and may consequently affect rhythm establishment and development. This research aimed to explore the influence of prenatal light exposure on the morphological alterations of retinal tissue, the expression of visual developmental signaling systems (TGF-β/Smad pathway), the expression of clock related genes (cClock, cBmal1, cBmal2, cAanat), and melatonin concentration in the chicken embryonic retina. Layer eggs (Jingfen No.6) were subjected to white light (5000K, WL) and green light (520 nm/515-525 nm, GL) with a 12L:12D photoperiod throughout the entire incubation period, in contrast to no light incubation (NL). The results showed that the thickness of retina and each retinal lamina of chicken embryo in WL at E20 was much thicker than that of chicken embryo in GL (P < 0.05). In contrary, the expression level of TGF-β1 mRNA and Smad2/3 protein in retina was dramatically downregulated in WL when compared to that in NL and GL (P < 0.01). Furthermore, the incubation light simultaneously significantly affected the diurnal rhythms of the chicken embryonic retina. The expression of three clock genes (cBmal1/2, cClock) and cAanat exhibited significant diurnal rhythms in GL (P < 0.05). Additionally, green light stimulation significantly enhanced melatonin secretion but did not show diurnal rhythm. However, cBmal1, cAanat, and melatonin expression exhibited diurnal rhythms (P < 0.01), while the others did not in WL. In NL, only cBmal1 exhibited diurnal rhythmicity (P < 0.01). In conclusion, providing light of different wavelengths during the incubation process of poultry can have varying effects on embryonic visual development and the establishment of diurnal rhythms. WL had an advantage to GL and NL on retina development and diurnal rhythm through significantly influencing the expression of genes related to visual developmental signaling pathways and clock genes. A well-developed retina in WL exposure chicken embryo may be beneficial for establishing a melatonin rhythm. Conversely, the established circadian rhythm could improve embryonic development.